Jadid modernism in Central Asia: the reformist vision of Abdurauf Fitrat - Ruxsatbegin To’ymurod-qizi Hojiyeva (Science and Education, 2026)
This article examines Jadid modernism in Central Asia through the reformist thought of Abdurauf Fitrat. While Jadidism is often described as a regional enlightenment movement, this study argues that it represented a structured intellectual response to colonial domination and social stagnation. Focusing on Fitrat’s educational and socio-political ideas, the research interprets his reformist vision as a localized model of Muslim modernism rather than a simple adaptation of Western paradigms. Using a historical and conceptual approach, the article demonstrates that Fitrat sought to reconcile tradition with modern rationality through educational transformation and civic awakening. His project aimed to reconstruct collective identity and promote social renewal. By situating Jadid modernism within broader debates on modernity and reform, the study contributes to expanding global perspectives on non-European modernist movements.